In situ synthesis of holey g-C3N4 nanosheets decorated by hydroxyapatite nanospheres as efficient visible light photocatalyst. Issue 50 (22nd September 2021) - Chahkandi, Mohammad; Zargazi, Mahboobeh; Ahmadi, Afsaneh; Koushki, Ehsan; Ghasedi, Arman
Abstract : The interesting g-C3 N4 nanosheet morphology has drawn huge attention in photocatalytic applications because of its special features. Abstract : The interesting g-C3 N4 nanosheet morphology has drawn huge attention in photocatalytic applications because of its special features. Nonetheless, the relative activity of these nanosheets is still controversial due to the low available active sites and the high recombination probability of photo-induced charge carriers. In this work, in situ sol–gel approach was applied to synthesize holey g-C3 N4 nanosheets/hydroxyapatite (HAp) nanospheres with plentiful in-plane holes. Herein, the presence of Ca 2+ plays a key role in the formation of holey defects on 2D g-C3 N4 . In-plane holes provide nanosheets with more active edges and diffusion channelsv, resulting in a tremendous enhanced mass and photo-induced charge transfer speed. Moreover, the holes make highly numbered boundaries, which lead to the prevention of aggregation. On the other hand, distributed nano-HAp spheres on these nanosheets can form effective heterojunctions having high photo-degradation ability of pollutants. Intrinsic O-vacancies inside HAp unit cells mainly affect the capture of photogenerated electrons, pollutant molecules, and O2 gas. The synergistic presence of O-vacancies and holey defects (C-vacancies) on 2D g-C3 N4 plays a key role in raising the photocatalytic performance of holey g-C3 N4 /HAp. It can be concluded that the proposed preparation method is a promising approach for simultaneous synthesis of holey g-C3 N4 and surface heterojunctions of Ca-based materials. This new structure has shown significant degradation ability of bisphenol A, a prominent pollutant, with a low amount (0.01 g) and short time.